FINANCING DECISIONS AND PERFORMANCE OF SMALL AND MEDIUM SCALE MAIZE MILLERS IN KENYA (Cuea Journal of Business and Economics, 2025)
Despite its role in the economic advancement of developing nations, the agribusiness industry is receiving a lot of flak for its lackluster performance. This research sought to determine how financing decisions influence the productivity of small and medium-sized maize millers in Kenya. The research used a cross-sectional descriptive survey approach and was based on the theories of planned behavior, financial control, and pecking order. The target group consisted of managers employed by the 255 small and medium-sized maize milling businesses that are registered in Kenya with the United Grain Millers Association. A census method was used.  The secondary data on performance in terms of total assets, return on assets and return on equity were offered by the annual financial statements, and the main data were collected through standardized questionnaire.  The capital budget cost and capital investment funds are mainly internally relied upon by the majority of the companies with minimal dependence on the stock market and the research established a positive and significant relationship between financial decision and the performance of the small and medium-sized maize millers in Kenya.  This study also found that the small and medium-sized maize millers in Kenya could get state assistance in terms of stock market funding on their activities.